The Role of Biotechnology in Improvement of Livestock - Abubakar, Muhammad (Springer, 2015)
This book examines how biotechnology can improve livestock breeding and farming, and thereby also animal products. In the first chapters the reader will discover which techniques and approaches are currently used to improve animal breeding, animal health and the value of animal products. Particular attention is given to reproduction techniques, animal nutrition and livestock vaccines that not only enhance animal health but also have a significant effect on human health by ensuring safe food procurement and preventing zoonotic diseases. In addition, modern biotechnology can increase not only productivity but also the consistency and quality of animal food, fiber and medical products.